Impacts of nighttime hypoxia on the physiological performance of Red Sea macroalgae under peak summer temperature - Taiba Alamoudi; Alexandra Steckbauer; Shannon G. Klein; Jacqueline V. Alva García; Silvia Arossa; Anieka J. Parry; Carlos M. Duarte (Frontiers in Marine Science, 2022)
Eutrophication-induced hypoxic sites are increasingly reported in coastal regions. At the same time, ocean warming, water column stratification, and changing circulation lead to open-ocean deoxygenation. In coastal areas and reefs with dense vegetation, aquatic organisms can be exposed to oxygen limitation stress where oxygen concentration reaches extremely low levels, particularly during nighttime once photosynthetic O 2 production has ceased. Despite scientists being aware of this for decades, little is known about the impact of deoxygenation on the physiology of marine primary producers, such as macroalgae. In the Red Sea, in particular, the physiological adaptations of macroalgae under future climate scenarios are nonexistent. Here, we investigate the impact of different oxygen levels (6.5, 2.5, and 1.3 mg O 2 L -1 ) at night for three conspicuous Red Sea macroalgae species Halimeda opuntia and Padina boryana (calcareous) and the brown algae Sargassum latifolium (noncalcifying). We monitored algal physiological responses during a 12-hour nighttime (dark) period at 32°C by measuring photochemical efficiency ( F v /F m ), respiration rates, and cellular viability. No lethal thresholds were detected. However, both deoxygenation treatments decreased respiration rates and induced changes in cellular activity, and only under severe hypoxia was a decrease in photochemical efficiency observed in all species. We calculated sublethal O 2 thresholds SLC (50) of 1.2 ± 0.1, 1.5 ± 0.1, and 1.7 ± 0.1 mg O 2 L -1 for H. opuntia , P. boryana , and S. latifolium , respectively. Therefore, the effects of nighttime hypoxia are evident over short timescales and may impact ecosystems via reduced primary production. Future consequences of persistent hypoxia and subsequent performance in multifaceted stressor exposures will provide a fundamental understanding of hypoxia’s threat to biodiversity and ecosystems.